Дослідження моделей та архітектурних рішень в базах даних Web-технологій - Чуприна, А. С.; Штельма, А. С. (ТОВ «Друкарня Мадрид», 2024)
The object of the study is databases, their models and architectural solutions that are used in web-technologies. The purpose of the work is to study the dependencies of models and architectural solutions for web-development.
Keywords: Web-технологія